Peri-Implant Bone Loss and Peri-Implantitis: A Report of Three Cases and Review of the Literature - Vanchit John; Daniel Shin; Allison Marlow; Yusuke Hamada (Hindawi Limited, 2016)
Dental implant supported restorations have been added substantially to the clinical treatment options presented to patients. However, complications with these treatment options also arise due to improper patient selection and inadequate treatment planning combined with poor follow-up care. The complications related to the presence of inflammation include perimucositis, peri-implant bone loss, and peri-implantitis. Prevalence rates of these complications have been reported to be as high as 56%. Treatment options that have been reported include nonsurgical therapy, the use of locally delivered and systemically delivered antibiotics, and surgical protocols aimed at regenerating the lost bone and soft tissue around the implants. The aim of this article is to report on three cases and review some of the treatment options used in their management.